(untitled) (Research, Society and Development, 2020)
Canine osteosarcoma is the most common bone tumor in dogs. It has an intense metastatic capacity, and the patient survival rate is low in this disease. Curcumin, the most important compound derived from the plant Curcuma longa L., has been widely studied and has shown considerable antineoplastic effects against many tumors. This study aims to identify the activation of specific proteins of apoptosis pathways, tumor survival, and poor prognosis of this disease in D-17 osteosarcoma cells. For this, the cells were cultured and treated with curcumin at concentrations of 20μM, 50 μM, and 100 μM in prepared and fixed slides. Subsequently, we performed the immunocytochemical analysis with anti-caspase3, anti-JNK, anti-AMPK, anti-p53, anti-AKT, and anti-mTOR antibodies. Curcumin activated the cell-death proteins caspase-3, JNK, and AMPK, reduced the expression of the mutated p53 protein, and did not alter the AKT and mTOR proteins in canine osteosarcoma cells in vitro. Thus, curcumin induces extrinsic apoptosis mediated by caspase, JNK, and cAMP/AMPK in canine osteosarcoma cells. Besides, it has the potential to improve the tumor prognosis of this disease by inactivating the mutated p53. However, it does not interfere with AKT/mTOR expression, related to tumor proliferation and survival. Such results will serve as a basis for future studies that analyze the effect of curcumin in vivo on this disease.